Development of First Aid Kit with Intuitive Touch Screen Display and Voice Instruction - Mahpar, Nor Fara Syahira; Jumadi, Nur Anida (Journal of Electronic Voltage and Application, 2021)
First aid kit has been used to treat minor pain or injuries before one can receive a qualified treatment from the medical doctor. It is found that the contents inside the first aid is only checked periodically and as a result, there is a high chance that certain important medicine is not there by the time it is needed. Thus, the development of smart first aid kit that prioritizes on content management via intuitive display and voice instruction is presented in this paper. The developed smart first aid kit offers several unique features. First is the use of infrared sensor to detect the availability of the first aid content. If the content is taken, the red LED will be lit up, and the user is notified through Blynk apps in smartphone and email by means of NodeMCU. Second feature is the developed first aid is equipped with the Smart TFT LCD touch screen display and speaker. This smart touch screen can display the list of first aid contents as well as provide a quick button for voice instructions. The voice instruction button will play the recorded guidance and medical instructions in the form of phrases and voices. The programming for the touch screen display, the voice instructions (played by Arduino Mini MP3 module) and speaker are all processed by the Arduino Mega. Simple testing and analysis on sensor detection and notification revealed that both sensor and Blynk app are working fine if the medications are placed in the correct position. In conclusion, a smart first aid kit with touch screen medications instructions menu equipped with voice instructions and the ability to alert the end user whenever the content of first aid is taken out has been successfully developed and executed in this study. All sensors and the programming for the touch screen and voice instruction are working accordingly. For future work, several improvements are recommended such as a better data management can be done which is by developing a database that can save the complete record on date, time, and name of the content that is taken out as well as alerting the user on expiry date. This can help the person in charge to efficiently monitor the content in the first aid.